Toward psychologies of liberation - Watkins, Mary 1950-; Shulman, Helene (Critical theory and practice in psychology and the human sciences, 2010)
A presentation of the theoretical foundation and participatory methodologies of psychologies of liberation that are emerging on every continent. The book proposes a radical interdisciplinary reorientation of psychology to aid in the creation of participatory and dialogical spaces for critical understanding and creative restoration.